(untitled) (Research, Society and Development, 2021)
This study deals with the role of nurses in the prevention of skin cancer in Primary Health Care. The objective is to highlight the importance of the professional nurse regarding the prevention of skin cancer in Primary Care. For this, the following guiding question was used: What is the importance of nurses in the prevention of skin cancer focused on Primary Health Care? As inclusion criteria, scientific articles were used between the years 2015 to 2020, in the databases, LILACS, SCIELO, BVS and BVS oncology in English, French and Spanish. As exclusion criteria, review articles outside the research time frame and that did not address the theme were excluded. The results obtained through the 18 selected scientific articles, brought into effect the elaboration of tree thematic categories, with the main focus being the role of nurses in the prevention of skin cancer in Primary Care. It is concluded that the role of nurses in primary care in raising awareness of the population about skin cancer and encouraging changes in behavior are of fundamental importance for its prevention.